PENGARUH FASILITAS LABORATORIUM DAN JOBSHEET PRAKTIK TERHADAP PRESTASI BELAJAR SISWA PADA MATAPELAJARAN PEMELIHARAAN CHASIS SEPEDA MOTOR SMK N 1 POSO PESISIR - Rezki Musbahin M.Tawahindo; Abdul Muis Mapalotteng; Yasser Abdul Djawad (Program Studi S2 Pendidikan Teknologi dan Kejuruan, 2023)
This study aims to examine and reveal the influence of laboratory facilities and practical job sheets on students’ learning achievement in Motorbcycle Chassis Maintenance subjects at SMKN 1 Poso Pesisir. The study is in the form of quantitative research, which aims to examine the influence of laboratory facilities and practical job sheets on students’ learning achievement in grade XI and XII of Motorcycle Engineering and Business. The research samples were 59 students of Motorcycle Engineering and Business. Data collection was conducted by using documentation, report cards, and questionnaires. The results of the study reveal that (1) the laboratory facilities are dominantly in very high category at 46%, (2) the practical job sheets are dominantly in very high category at 34%, (3) the students’ learning achievement in Motorcycle Chassis Maintenance subject obtain a fairly high score which is 64% in average, (4) there is a significant positive influence between the laboratory facility variable (X1) on learning achievement, (5) there is a significant negative influence between the practice job sheet variable (X2) on learning achievement, and (6) there is a significant positive influence between the laboratory facilities variable (X1) and practical job sheets (X2) collectively on students’ learning achievement in Motorcycle Chassis Maintenance subject at SMKN 1 Poso Pesisir.